Necropolítica e educação: a guerra continuada por outros meios - Barbosa, Leandro Alves (2020)
The aim of this work is to approach the concept of necropolitics in the thought of Achille Mbembe from the author's works and interviews, his conceptual relationship with Michel Foucault, Carl Schmitt, Frantz Fanon, Giorgio Agamben, Gilles Deleuze and Felix Guattari, Édouard Glissant, and with Latin and African-American thinkers, based on the idea of race as a device, a technology of power, of life management, structuring modernity / coloniality, according to the Modernity/Coloniality Group, precursor of thought or decolonial turn in post- Latin American colonials. This idea, of the centrality of race to thought and to the formation of modernity, fundamental to necropolitics, as well as modern and contemporary colonialism, will be articulated in order to think about education in Brazil in dialogue with Abdias do Nascimento, Sueli Carneiro, Boaventura de Sousa Santos, Eliseu Pessanha, Sylvio Gadelha, Bernadete Beserra and Rémi Lavergne. We argue that the necropolitics is a war policy that has its genealogy in colonial slavery and uses racial subsidies for the physical elimination of bodies, their cultures and ways of thinking. It is in this line that we concentrated our exhibition, thinking about the relationship between necropolitics and education while the war continued by other means. The methodology adopted is bibliographic research.